Association of Endothelial Dysfunction with Endothelin, Nitric Oxide and eNOS Glu298Asp Gene Polymorphism in Coronary Artery Disease. Issue 4 (27th May 2013) - Saini, Vandana; Bhatnagar, M. K.; Bhattacharjee, Jayashree
Abstract : The endothelial dysfunction has been implicated as a major event in the pathogenesis of atherosclerosis. Therefore, this study was planned to determine (a) role of endothelium-derived nitric oxide (NO) and endothelin as coronary artery disease (CAD) risk markers and (b) intergenotypic variation of endothelial nitric oxide synthase (eNOS) Glu298Asp polymorphism in CAD.The endothelin, NO and eNOS genotypes were determined in 60 patients with documented history of CAD. These were compared with 50 age- and sex- matched healthy controls. The genotype frequencies for eNOS gene polymorphism were determined by PCR and RFLP. The plasma endothelin in CAD patients was significantly higher ( p < 0.001) whereas, the NO level in CAD group was significantly lower ( p < 0.001) than the control group. The genotype frequencies for Glu298/Asp (Glu/Glu and Glu/Asp) genotypes were 75% and 25% in CAD subjects and 88% and 12% in control subjects, respectively. No Asp/Asp was found in any of the groups. The genotype frequencies differed significantly ( p < 0.05) between the controls and cases. In conclusion, endothelin and NO may be used as markers of endothelial dysfunction in CAD. Asp allele might be a risk factor for CAD in the North Indian population.